2022
DOI: 10.1038/s41467-022-30863-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B cell repertoire defects predispose lung cancer patients to immune-related toxicity following checkpoint blockade

Abstract: Checkpoint blockade with Pembrolizumab, has demonstrated durable clinical responses in advanced non-small cell lung cancer, however, treatment is offset by the development of high-grade immune related adverse events (irAEs) in some patients. Here, we show that in these patients a deficient Breg checkpoint fails to limit self-reactive T cell enhanced activity and auto-antibody formation enabled by PD-1/PD-L1 blockade, leading to severe auto-inflammatory sequelae. Principally a failure of IL-10 producing regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 73 publications
0
16
0
1
Order By: Relevance
“…A longitudinal assessment of blood in an advanced lung cancer patient who developed late-onset irAEs on PD-1 inhibition, also reported increases in plasmablasts in circulation ( 119 ). Using functional ex vivo assays and mass cytometry analysis, defects in the regulatory B cell repertoire was found to predispose NSCLC patients to the development of immune related toxicity following anti-PD-1(L1) blockade ( 120 ). Notably, an attenuated presence of circulatory immunosuppressive B cell subsets (IL-10+, TGF-B+ PDL-1+) was observed in patients that developed toxicities compared to those that did not.…”
Section: Autoantibodies and B Cells As Biomarkers Of Immune Related A...mentioning
confidence: 99%
“…A longitudinal assessment of blood in an advanced lung cancer patient who developed late-onset irAEs on PD-1 inhibition, also reported increases in plasmablasts in circulation ( 119 ). Using functional ex vivo assays and mass cytometry analysis, defects in the regulatory B cell repertoire was found to predispose NSCLC patients to the development of immune related toxicity following anti-PD-1(L1) blockade ( 120 ). Notably, an attenuated presence of circulatory immunosuppressive B cell subsets (IL-10+, TGF-B+ PDL-1+) was observed in patients that developed toxicities compared to those that did not.…”
Section: Autoantibodies and B Cells As Biomarkers Of Immune Related A...mentioning
confidence: 99%
“…B-cell depletion with the anti-CD20 monoclonal antibody rituximab has shown some promise for dermatological irAEs, with no apparent adverse impact on survival ( 104 ), and observations in inflammatory arthritis reviewed above arguably support interest in the approach. This should, however, be balanced against the general dearth of infiltrating B-cells in irAE tissues described herein, together with very recent data indicating that regulatory B-cells (Bregs), which would also be targeted by an anti-CD20 strategy, may play a critical role in the prevention of irAEs ( 105 ). A deficiency of this cell type in the circulation of CPI recipients was indeed predictive of subsequent toxicity in this study.…”
Section: Conclusion and Therapeutic Considerationsmentioning
confidence: 83%
“…Early diversification of T cell repertoire with decline in T cell clonality, increase in Th17 cells or early B cell changes have all been found to be associated with early development of irAE [82][83][84][85] . Deficiency in certain regulatory B cell phenotypes was found in patients who developed serious irAE 86 . Chaput et al showed that the composition of gut microbiota with Faecalibacterium and other Firmicutes has been associated with ipilimumab-induced colitis, whereas, the presence of Bacteroidetes was protective against colitis 87 .…”
Section: Developing a Predictive Model Of Irae For Use In Clinical Pr...mentioning
confidence: 99%